The BEAN experiment - An EISCAT study of ion temperature anisotropies - I. W. McCrea; G. O. L. Jones; M. Lester (Annales Geophysicae, 1995)
Results are presented from a novel EISCAT special programme, SP-UK-BEAN, intended for the direct measurement of the ion temperature anisotropy during ion frictional heating events in the high-latitude F-region. The experiment employs a geometry which provides three simultaneous estimates of the ion temperature in a single F-region observing volume at a range of aspect angles from 0° to 36°. In contrast to most previous EISCAT experiments to study ion temperature anisotropies, field-aligned observations are made using the Sodankylä radar, while the Kiruna radar measures at an aspect angle of the order of 30°. Anisotropic effects can thus be studied within a small common volume whose size and altitude range is limited by the radar beamwidth, rather than in volumes which overlap but cover different altitudes. The derivation of line-of-sight ion temperature is made more complex by the presence of an unknown percentage of atomic and molecular ions at the observing altitude and the possibility of non-Maxwellian distortion of the ion thermal velocity distribution. The first problem has been partly accounted for by insisting that a constant value of electron temperature be maintained. This enables an estimate of the ion composition to be made, and facilitates the derivation of more realistic line-of-sight ion temperatures and temperature anisotropies. The latter problem has been addressed by assuming that the thermal velocity distribution remains bi-Maxwellian. The limitations of these approaches are discussed. The ion temperature anisotropies and temperature partition coefficients during two ion heating events give values intermediate between those expected for atomic and for molecular species. This result is consistent with an analysis which indicates that significant proportions of molecular ions (up to 50%) were present at the times of greatest heating.